An Error Analysis of EFL Students’ English Writing - Andrian Andrian (Universitas Syiah Kuala, 2015)
The objective of this study was to find out the category of errors that EFL students usually made in their writings at Business College LP3I, Banda Aceh. The subjects of this study were two classes of fourth semester students from the Office Management and Computerized Information majors which had a total of 17 students. The data was collected through quantitative method. The instrument used to collect the data was tests. The findings of the study showed that the highest percentage of errors was from the category of tenses, including subject verb agreement. The lowest percentage of errors was from the category of clauses and phrases (conditional, wish, reported/quoted speech). It is suggested that the teacher could have conducted brainstorming with the students first before the writing assignment was given so that they can be assisted in vocabulary choices to use in their writing. The students should also be trained with more rules of grammar needed by beginners such as simple tenses, determiners, usage of idioms and the like.